Long-term spatial and temporal trends in frost indices in Kansas, USA - Anandhi, Aavudai; Perumal, Sriram; Gowda, Prasanna H.; Knapp, Mary C.; Hutchinson, Stacy L.; Harrington, John A., Jr.; Murray, Leigh W.; Kirkham, Mary B.; Rice, Charles W. (My University, 2013)
Frost indices such as number of frost days (nFDs), number of frost-free days (nFFDs), last spring freeze (LSF), first fall freeze (FFF), and growing-season length (GSL) were calculated using daily minimum air temperature (T[subscript min]) from 23 centennial weather stations across Kansas during four time periods (through 1919, 1920–1949, 1950–1979, and 1980–2009). A frost day is defined as a day with T[subscript min] < 0 °C. The long- and short-term trends in frost indices were analyzed at monthly, seasonal, and annual timescales. Probability of occurrence of the indices was analyzed at 5 %, 25 %, 50 %, 75 %, and 95 %. Results indicated a general increase in T[subscript min] from 1900 through 2009 causing a decrease in nFDs. LSF and FFF occurred earlier and later than normal in the year, respectively, thereby resulting in an increase in GSL. In general, northwest Kansas recorded the greatest nFD and lowest T[subscript min], whereas southeast Kansas had the lowest nFD and highest T[subscript min]; however, the magnitude of the trends in these indices varied with location, time period, and time scales. Based on the long-term records in most stations, LSF occurred earlier by 0.1–1.9 days/decade, FFF occurred later by 0.2–0.9 day/decade, and GSL was longer by 0.1–2.5 day/decade. At the 50 % probability level, Independence in the south-eastern part of Kansas had the earliest LSF (6 April), latest FFF (29 October) and longest GSL (207 days). Oberlin (north-western Kansas) recorded the shortest GSL (156 days) and earliest FFF (7 October) had the latest LSF (2 May) at the 50 % probability level. A positive correlation was observed for combinations of indices (LSF and GSL) and elevation, whereas a negative correlation was found between FFF and elevation.
Citation: Anandhi, A., Perumal, S., Gowda, P.H. et al. Climatic Change (2013) 120: 169. https://doi.org/10.1007/s10584-013-0794-4
Keywords: Frost indices; Kansas; Climate change